Expression of Central Glucocorticoid Receptors after Peripheral Nerve Injury Contributes to Neuropathic Pain Behaviors in Rats - Wang, Shuxing (J Neurosci, 2004)
Peripheral glucocorticoid receptors (GRs) play a significant role in the anti-inflammatory effects of glucocorticoids; however, the role of central GRs in nociceptive behaviors after peripheral nerve injury (neuropathic pain behaviors) remains unknown. Here we show that the development of neuropathic pain behaviors (thermal hyperalgesia and mechanical allodynia) induced by chronic constriction nerve injury (CCI) in rats was attenuated by either the GR antagonist RU38486 (4 = 2 > 1 = 0.5 μg) or a GR antisense oligonucleotide administered intrathecally twice daily for postoperative days 1-6. The development of thermal hyperalgesia and mechanical allodynia after CCI also was prevented in adrenalectomized rats, whereas the GR agonist dexamethasone (100 μg/kg) given subcutaneously twice daily for postoperative day 1-6 restored CCI-induced neuropathic pain behaviors in the adrenalectomized rats. Mechanistically, CCI induced a time-dependent and region-specific expression of neuronal GRs primarily within the spinal cord dorsal horn ipsilateral to nerve injury, which showed a time course parallel to that of the development of neuropathic pain behaviors. Moreover, the expression of neuronal GR after CCI was mediated in part through an elevated spinal level of interleukin-6 (IL-6) and protein kinase Cγ (PKCγ), because intrathecal treatment with an IL-6 antiserum, a PKC inhibitor (cheryrithrine), or PKCγ knock-out substantially reduced the expression of neuronal GRs as well as neuropathic pain behaviors after CCI. These findings indicate a central role of neuronal GRs in the mechanisms of neuropathic pain behaviors in rats and suggest a potential role for GR antagonists in clinical management of neuropathic pain.